‘Woman Suffrage Precipice’: The Gender Politics of Laughter in Elizabeth Robins’s The Convert (1907) - Nathalie Saudo-Welby (Cahiers Victoriens et Edouardiens)
An actress turned playwright and political militant, Elizabeth Robins was aware of the political uses of laughter. Her novel The Convert, in which laughter is explicitly linked to performance and action, is stimulating material for an investigation of the part played by humour in women’s empowerment. The New Woman was often criticized for her lack of humour, and gravity was the expected context of feminist novels with a purpose. Elizabeth Robins wanted her political drama Votes for Women to “deal with the Suffrage question for the first time in a serious fashion”. Yet, when the play was transformed into a novel, The Convert, comedy became a central element in the representation of female suffrage. Indeed, since the New Woman was commonly a target for caricature, the suffragette a laughing stock, and feminist demonstrations were considered as enjoyable as “good Sunday afternoon street entertainment”, The Convert turned this tendency to its advantage and used humour as a sweetener for the serious pill it contains, in accordance with the received idea that women are born entertainers. In the witty drawing-room conversations and in the sarcastic call and response exchanges during the demonstration scenes, Elizabeth Robins also builds up a reflection on the gender politics of humour. Her didactic novel indicates that not all laughter is “good to hear” and that feminist literature must bring some laughs to a halt. More crucially, it suggests that while men laugh, women may learn. The loudness of the laughing response is proportionate to the gravity and magnitude of the woman question. In the course of her conversion into a suffragette, Vida gets a sense of her political significance, builds up her armour and turns her sense of repartee into a political weapon.